In the Eye of the Beholder: Effects of Parent-reported Parenting and Adolescent-reported Parenting on Identity among German and Zambian Adolescents. Issue 2 (3rd April 2021) - Lehmann, Meike; Hofer, Jan; Busch, Holger; Menon, Javasree Anitha
ABSTRACT: While a substantial number of studies have shown that perceived parenting plays an important role in identity formation, research employing a multi-informant and cross-cultural approach is still lacking. Attempting to fill this gap, we hypothesized that adolescent-reported parenting mediates the link between parent-reported parenting and identity dimensions (i.e., commitment, in-depth exploration, and reconsideration of commitment) in German and Zambian samples. In total, 731 adolescents ( n Zambia  = 244; M Age  = 14.68; 47% female) and their parents ( M Age  = 45.55; 82% female) completed questionnaires on parenting (Alabama Parenting Questionnaire) and identity (Utrecht-Management of Identity Commitments Scale; adolescents only). Regarding positive parenting, in both the German and the Zambian sample, an indirect effect of parent-reported parenting via adolescent-reported parenting on commitment, in-depth exploration, and reconsideration of commitment was found. For negative parenting, there were indirect effects on in-depth exploration and reconsideration of commitment, but no indirect effect was found for commitment. Taken together, our results suggest that adolescents' subjective experience of parenting represents the significant element that impacts adolescents' identity formation.